Revisiting the Pathoetiology of Multiple Sclerosis: Has the Tail Been Wagging the Mouse? - Sen, Monokesh K.; Almuslehi, Mohammed S. M.; Shortland, Peter J.; Coorssen, Jens R.; Mahns, David A. (Frontiers in Immunology, 2020)
Multiple Sclerosis (MS) is traditionally considered an autoimmune-mediated demyelinating disease, the pathoetiology of which is unknown. However, the key question remains whether autoimmunity is the initiator of the disease (outside-in) or the consequence of a slow and as yet uncharacterized cytodegeneration (oligodendrocytosis), which leads to a subsequent immune response (inside-out). Experimental autoimmune encephalomyelitis has been used to model the later stages of MS during which the autoimmune involvement predominates. In contrast, the cuprizone (CPZ) model is used to model early stages of the disease during which oligodendrocytosis and demyelination predominate and are hypothesised to precede subsequent immune involvement in MS. Recent studies combining a boost, or protection, to the immune system with disruption of the blood brain barrier have shown CPZ-induced oligodendrocytosis with a subsequent immune response. In this Perspective we review these recent advances and discuss the likelihood of an inside-out vs an outside-in pathoetiology of MS.